Perbedaan Motivasi Belajar Peserta Didik Laki-Laki Dan Perempuan - Fanani, Achmad Risqi Fanani; Zuhroh, Luthfiatuz (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Junior high school teachers think that the learning achievement of female students is higher than that of male students because students' motivation to learn is higher than that of students. but is it true that the learning motivation of female students is higher than that of male students. This study aims to determine the level of differences in students' learning motivation in terms of gender. Using comparative research method, Mann Whitney test, distribution of trend level and class interval to compare which variable is higher and lower. In the end, it was concluded that there was no significant difference in the results of the study of learning motivation. Comparison of the average scores obtained by male and female students also shows that students are superior only by 1 frequency difference. Most of the students' learning motivation levels are at the middle level.